2015
DOI: 10.1007/s13562-015-0298-6
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation analysis of sterile and fertile CMS-C hybrids and their parents in maize

Abstract: C-type cytoplasmic male sterile (CMS-C) line plays an important role in hybrid seed production in maize. However, mechanisms of pollen abortion and fertility restoration remain unclear. This study aimed to investigate the mechanisms of CMS-C pollen abortion and fertility restoration, particularly based on epigenetics, and to understand the relationship between male fertility performance and DNA methylation status. Methylation-sensitive amplification polymorphism (MSAP) technique was conducted to analyze DNA me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Some studies have found altered methylation patterns in male sterile plants and evidence that methylation regulates EGMS in rice [23,24,25], CMS in rice [26] and maize [27] and GMS in tomato [28] and wheat [29]. However, to date, no study has reported these methylation profiles and their possible roles in the cabbage male sterility line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have found altered methylation patterns in male sterile plants and evidence that methylation regulates EGMS in rice [23,24,25], CMS in rice [26] and maize [27] and GMS in tomato [28] and wheat [29]. However, to date, no study has reported these methylation profiles and their possible roles in the cabbage male sterility line.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al observed higher DNA methylation levels in maize fertility-restored hybrids than in maize sterility-maintained hybrids and detected a specific site (16–1) in one of the restorer genes, Rf5 [27]. This finding suggests that DNA methylation may regulate the expression of fertility restorer genes.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence has shown that dynamic changes in DNA methylation may mediate transcriptional variation during male reproductive development [35,36]. Over the past several years, the association of DNA methylation status with CMS or genic male sterility (GMS) has been reported in many plants, such as rice [37], wheat [38], maize [39], cotton [35,40], cabbage [41], and tomato [42]. These observations suggest that disrupted genomic DNA methylation in response to high-temperature stress disturbs sugar and ROS metabolism, ultimately resulting in microspore abortion in GMS cotton [35].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in DNA methylation have been shown to play a crucial part in plant stress responses [6]. Additionally, some recent reports revealed that DNA methylation levels are affected by DMTs and regulated the expression of genes involved in cytoplasmic male sterile in rice, maize, and wheat [56][57][58]. However, few studies have been reported about exploring the roles of DMTs in TGMS wheat during the reproductive stage.…”
Section: Introductionmentioning
confidence: 99%